Clinicopathological significance of CADM4 expression in invasive ductal carcinoma of the breast. Issue 8 (4th April 2013) - Jang, Se Min; Sim, Jongmin; Han, Hulin; Ahn, Hye In; Kim, Hyunsung; Yi, Kijong; Jun, Young Jin; Rehman, Abdul; Chung, Min Sung; Jang, Kiseok; Paik, Seung Sam
Abstract : Aims: Cell adhesion molecule 4 (CADM4) is a novel tumour suppressor involved in cell adhesion. Loss or decreased expression of CADM4 has been associated with the development and progression of some cancers. The purpose of this study was to investigate the clinicopathological significance of CADM4 expression in breast cancer. Methods: We constructed tissue microarrays to evaluate the immunohistochemical expression of CADM4 in 256 cases of invasive ductal carcinoma (IDC) and 45 cases of ductal carcinoma in situ (DCIS). Results: CADM4 was expressed in 37 (82.2%) DCIS cases, and in 173 (67.6%) IDC cases. CADM4 expression was higher in DCIS than in IDC (p=0.049). Loss or decrease of CADM4 expression was significantly correlated with higher histological grade (p=0.020), absence of oestrogen receptors (p<0.001), absence of progesterone receptors (p=0.024), and overexpression of c-erbB-2 (p=0.018). In univariable and multivariable Cox regression analyses of all 256 IDC cases, CADM4 expression was not significantly associated with overall and disease-free survival. However, it showed a significant positive association with longer disease-free survival in 187 stages I and II IDC cases (p=0.039, log-rank test). Conclusions: Loss or decrease of CADM4 expression seems to play an important role in breast cancer invasiveness, and it is associated with poorer biological parameters. CADM4 can be used as a novel marker predicting risk of recurrence and disease outcomes in stages I and II IDC.